2016
DOI: 10.3389/fpsyg.2016.00269
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Alcohol Use in Spain: Connections with Friends, School, and Other Delinquent Behaviors

Abstract: This study examined the connections between adolescent alcohol use in Alicante, Spain and variables reflecting adolescents’ academic problems, potentially delinquent behaviors, friends’ alcohol consumption, and friendship quality. Information about alcohol use and a number of school and social variables was collected from adolescent students (N = 567) who completed the National Students School-Based Drug Survey in a classroom setting. Results suggested that gender was not significantly associated with alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 37 publications
(69 reference statements)
4
23
0
3
Order By: Relevance
“…The present findings show that students who had missed classes without permission in the 30 days prior to the study demonstrated a more-than-twofold increase in alcohol consumption. This trend is consistent with previous findings that truant students are more likely to report alcohol consumption and alcohol-related problems than non-truant students [25][26][27]. Truancy is linked to an unfavourable educational environment and physical or mental disability among students.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings show that students who had missed classes without permission in the 30 days prior to the study demonstrated a more-than-twofold increase in alcohol consumption. This trend is consistent with previous findings that truant students are more likely to report alcohol consumption and alcohol-related problems than non-truant students [25][26][27]. Truancy is linked to an unfavourable educational environment and physical or mental disability among students.…”
Section: Discussionsupporting
confidence: 92%
“…Omega is based on the common variance and represents the ratio of the true-score variance to the total variance (ω = (Σ|λ i |) 2 /([Σ|λ i |] 2 + Σδ ii ), where λ i are the standardized factor loadings, δ ii the standardized item uniqueness and i subscript denotes a particular item of the scale). Contrary to alpha coefficient, omega does not require equal factor loadings or uncorrelated error variances (Dunn et al, 2014 ; Trizano-Hermosilla and Alvarado, 2016 ). As a result, ω takes into account the strength of the association between the indicators and the construct as well as the item specific measurement bias.…”
Section: Resultsmentioning
confidence: 99%
“…More generally, a negative attitude toward school is, in fact, a risk factor for aggressive behaviors ( Estévez et al, 2014 ). Conversely, school connectedness, engagement, academic achievement, and academic enjoyment may protect against alcohol use, suspension, lower educational aspirations, and poor academic performance ( Goldberg-Looney et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, school failure is related to alcohol consumption. A study conducted by Goldberg-Looney et al (2016) found that academic problems explained 5.1% of the variance in adolescents’ alcohol use in a sample of 567 adolescents in Spain.…”
Section: Introductionmentioning
confidence: 99%